Simulation of the Liquid–Solid Coupling in the Distribution Law of Water-Conducted Fractures in Weakly Cemented Overburden Strata as Exemplified by Daliuta Coal Mine in Western China - Yangyang Li; Boming Zhang; Shichuan Zhang; Xuexian Han; Weihong Yang; Haibin Wang; Chuanwei Jia (Geofluids)
Based on the engineering background of the Daliuta mining area, the distribution of fractures and movement of water within weakly cemented overlying strata were studied with a physical simulation of liquid–solid coupling and a COMSOL numerical simulation test. The results showed that after the initial caving of the roof, all kinds of fractures rapidly developed in the overburden in the longitudinal direction, forming longitudinal fractures on opposite sides of the working face with angles of 81° and 78°; the space between the separated strata became the main channel for water flow. Under the action of water flow and the movement of the rock strata, mining-induced fractures in the overlying rock displayed cyclic changes in the form of expansion, penetration, and closure. When the working face was fully mined, the penetrating fractures in the overlying strata and the mining-induced fractures in the working face became the main passages for water flow. The results of the numerical simulation showed that the seepage rate of overburden water increased with the advancement of the working face. When the working face advanced to 120 m, the attenuation of pressure and the increase in the seepage velocity were significantly slowed down. These experimental results provide a reference for the layout and maintenance of underground reservoirs and water-conserved mining in Western China.